2001
DOI: 10.1086/317936
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution ofCandidaSpecies and Fluconazole Susceptibility among Oral and Vaginal Isolates Recovered from Human Immunodeficiency Virus (HIV)–Seropositive and At‐Risk HIV‐Seronegative Women

Abstract: Antifungal agents can effectively treat mucosal candidiasis; however, their use can lead to colonization with less susceptible species and to resistance among normally susceptible strains. Oral and vaginal Candida isolates obtained at 3 points over 2 years from human immunodeficiency virus (HIV)-seropositive and at-risk HIV-seronegative women were identified by species and were evaluated for in vitro fluconazole susceptibility. Prevalence of non-C. albicans strains increased over time, and these strains were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 36 publications
4
44
1
1
Order By: Relevance
“…In other countries such as Italy and the United States, the frequency was higher ranging from 81% to 92%, compared to that found in our study (52.9%). 10,11,18 In HIV-uninfected patients, our data was similar to other studies performed in Brazil, which describe the prevalence of C. albicans isolated in vaginal samples ranging from 60% to 80% 19,20 and in other countries where the prevalence of C. albicans in vaginal samples ranges between 80% to 90%. 1,11,21,22 A higher diversity of non-albicans species was found in HIV-infected patients compared to uninfected controls.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In other countries such as Italy and the United States, the frequency was higher ranging from 81% to 92%, compared to that found in our study (52.9%). 10,11,18 In HIV-uninfected patients, our data was similar to other studies performed in Brazil, which describe the prevalence of C. albicans isolated in vaginal samples ranging from 60% to 80% 19,20 and in other countries where the prevalence of C. albicans in vaginal samples ranges between 80% to 90%. 1,11,21,22 A higher diversity of non-albicans species was found in HIV-infected patients compared to uninfected controls.…”
Section: Discussionsupporting
confidence: 89%
“…9,10 The frequency of VVC caused by other Candida species, such as Candida tropicalis, Candida glabrata, and Candida krusei is increasing, especially in HIV-infected women. 5,8,11 C. albicans and C. glabrata are responsible for the majority of VVC cases in HIV-infected women. 10,12 Although resistance to azoles antifungal therapy is rare in C. albicans isolates (1%), it is becoming commonplace among C. glabrata isolates (up to 15%) as well as among other non-albicans species.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional and cohort studies have shown only a moderate increase in Vulvovaginal candidosis in HIVpositive women not receiving antiretroviral therapy compared with HIVnegative women (Schuman et al, 1998;Sobel et al, 2001) and the increased incidence of vulvovaginal candidosis in HIV-positive women compared with HIV-negative women was modest compared with the increase in the occurrence of oropharyngeal candidosis. The microbiology of vulvovaginal candidosis in HIVpositive women seems to be identical to that of matched high-risk HIV-negative women, although with time and possible unmeasured azole exposure there is a tendency to isolate non-albicans Candida spp, notably C glabrata and candida isolates with reduced sensitivity to fluconazole.…”
Section: Vulvovaginal Candidiasis In Hiv-positive Womenmentioning
confidence: 99%
“…11 Development of resistance to fluconazole in immunocompromised patients has become an issue of growing concern and is usually correlated to the degree of immunosuppression and the total dose of drug used in long-term antifungal treatments. 12,13 There are several reports of the prevalence of Candida species in patients with fungal infections in Argentina. [14][15][16][17][18][19][20][21][22] However, there has been only one study about oral carriage of Candida species carried out by Negroni et al [23] on population of students.…”
Section: Introductionmentioning
confidence: 99%